Ecosystem services mapping and modelling. Where is the validation? - Paulo Pereira; Miguel Inacio; Damia Barcelo; Wenwu Zhao (Geography and Sustainability)
Ecosystem services (ES) mapping and models have advanced in recent years. Improvements were made, and the assessments have transitioned from qualitative to quantitative. Although this is an important advancement, the ES mapping and modelling validation step has been overlooked, and this raises an important question in the credibility of the outcomes. This has been an important and unsolved issue in the ES research community that needs to be tackled. This highlight paper discusses the importance of validating single ES mapping and models. Conducting this using field or proximal/remote sensing raw data and not data from other models or stakeholder evaluation is important. A validation step should be mandatory in ES frameworks since it can assess the models’ veracity, contribute to identifying the model’s weaknesses/strengths and ultimately represent a scientific advance in the field. This is easier to apply to the biophysical mapping and models of regulating and provisioning ES than to cultural ES, as the latter rely more on perception and cultural contexts. Also, ES supply models are easier to validate than demand and flow models. Robust and well-grounded models are essential for ensuring the reliability of individual ES maps and models and should be integrated into decision-making processes. Although several challenges arise related to the costs of data collection, in several cases prohibitive, and the time and the expertise needed to conduct this sampling and analysis, this is likely an imperative step that needs to be considered in the future. This will be beneficial in establishing ES research and improving decision-making and wellbeing.